Immunosuppression of spleen in mice treated with erythropoietin: transcriptomic and immunological analysis - Lyu, Xinyi; Shi, Jiahao; Liu, Qi; Jiang, Mingjun; Liu, Xilian; Li, Yulan; Ding, Shuqin; Dai, Xianpeng (Frontiers in Immunology, 2025)
Background and aimLong term high-dose erythropoietin (EPO) had been reported inducing the formation of abdominal aortic aneurysm (AAA) in mice. When using this model, we found that EPO treated mice showed significant splenomegaly. This is an interesting phenomenon, and its mechanism has not been reported. Therefore, this study aims to explore its mechanism.MethodsC57BL/6 mice were given intraperitoneal injection of recombinant human EPO at 10000 IU/kg/day, and the control mice were treated with normal saline (vehicle). After 3 weeks, the spleens were harvested. Pathological changes in histology were observed using Hematoxylin and Eosin (H&E) staining. The differential expression genes (DEGs) were identified using RNA sequencing (RNA-Seq), verified with the real-time quantitative polymerase chain reaction (RT-qPCR). The functional-enrichment analysis including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Reactome enrichment analysis were performed to reveal the functional characteristics and related biological pathways of DEGs. Immunohistofluorescence (IHF) and flow cytometry (FCM) were used to detect immune cell subsets and proliferation markers.ResultsEPO treatment resulted in splenomegaly, spleen microstructure disorder, splenic corpuscular atrophy, indistinct germinal center, and unclear boundary between white and red pulp structures. RNA-Seq showed that EPO treatment suppressed gene expression associated with immune responses, while promoted cell cycle and DNA replication. IHF and FCM validated that, at the cellular level, T, B, M1 cells were significantly reduced, and M2 cells were significantly decreased after EPO treatment. The proliferation analysis showed that the portion of EDU+ or Ki-67+cells consisted of granulocytes and macrophages, and after EPO treatment, only macrophages showed a significant increase in their number and proportion, while granulocytes did not show a significant response to EPO stimulation.ConclusionLong term high-dose EPO treatment may lead to splenomegaly and immunosuppression of the local immune microenvironment in mice. The mechanism may be related to the increased anti-inflammatory and immunomodulatory functions caused by M2 cells. The study provides, for the first time, the transcriptomic characteristics and immunological of the spleens of EPO treated mice, providing a new perspective for the study of the effects of EPO on mice.